Effect OF POTASSIUM AND MULCHES ON GROWTH, YIELD AND ECONOMICS OF POTATO - Pulok, Md. Ashraful Islam; Roy, Tuhin Suvra; Rashid Bhuiyan, Md. Shahidur; Haque, Md. Nazmul; Nur-unnahar, Nur-unnahar (Potato Journal, 2017)
Â Â Â